2000
DOI: 10.1093/molehr/6.3.276
|View full text |Cite
|
Sign up to set email alerts
|

VEGF, its receptors and the Tie receptors in recurrent miscarriage

Abstract: The aetiology of recurrent miscarriage (at least three consecutive miscarriages) usually remains unsolved. The vascular endothelial growth factor (VEGF) family of proteins, together with their receptors and the Tie (tyrosine kinase with immunoglobulin and epidermal growth factor homology domains) receptors, are crucial for embryonic development. Therefore, we used immunohistochemistry to analyse the expression of VEGF, the VEGF receptors (VEGFR)-1, -2, and -3, and the Tie-1 and Tie-2 receptors in placental and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
73
2
4

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(88 citation statements)
references
References 8 publications
7
73
2
4
Order By: Relevance
“…The human placenta is rich in angiogenetic growth factors including vascular endothelial growth factor (VEGF), which plays an important role in regulation of forming placental vessels. The role of VEGF family in embryonic development, trophoblast vascularization were reported (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…The human placenta is rich in angiogenetic growth factors including vascular endothelial growth factor (VEGF), which plays an important role in regulation of forming placental vessels. The role of VEGF family in embryonic development, trophoblast vascularization were reported (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Demir et al (29) sugessted that expression of VEGF and its receptors VEFR-1 and VEGFR-2, and angiopoietin receptors Tie-1 and Tie-2 in parallel to vascular maturation in human placental villi during very early stages of placental development. Vuorela et al (31) described diminished placental trophoblastic VEGF immunoreactivity, reduced placental trophoblastic Tie-1 and Tie-2 expression and weaker VEGFR-1, VEGFR-2,Tie-1 and Tie-2 expression in decidual endometrium of spontaneous abortions and these results are similar of our results in which we found that the cytotrophoblasts and syncytiotrophoblasts of the placental villi and endometrial gland cells stained significantly more weakly for VEGF in the patient groups (IA and IU-D) in comparison to the controls. And also they found weak immunostaining for VEGF in vascular endothelium of the placental villi of the healthy controls similar with our study.…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, the authors showed that, for both VEGF-A and its receptor VEGFR-2 (KDR/flk-1), this stage corresponded to the transition from secondary villi to tertiary villi, which also occurs at 21-32 days post conception (33). The soluble form of VEGF (VEGRF-1) and placental growth factor (PIGF) are expressed during later stages (branching angiogenesis phase), i.e., between 32 days and 25 weeks of gestation (28)(29)(30)(31)(32)(33). Therefore, the levels of serum (soluble) VEGF would not be suitable to predict early pregnancy loss.…”
Section: Discussionmentioning
confidence: 99%
“…69 Studies show that a different pattern of expression of angiogenic growth factor is involved in recurrent miscarriage. 70 As with most human studies, whether the unregulated genetic expression of angiogenic growth factor were responsible for a nature of miscarriages is difficult to determine with certainty. There are two mechanisms involved in the formation of blood vessels: vasculogenesis and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%